Sistema Web y aplicación android para la gestión de las actividades de voluntariado de la Universidad Politécnica Salesiana, Sede Quito. - Gahona Delgado, Roddy Vinicio (2017)
With the development of the project, the detail of which is described in this document, it has been sought to apply all the knowledge acquired in the engineering career of systems, developing a web system and a mobile application that serves the technical direction of Pastoral headquarters Quito as automation tools for Social action volunteering, allowing them to have two platforms that can be accessed from anywhere and at any time, facilitating the process of registration and monitoring of Students for each academic period. On the other hand, the Technical Directorate of Pastoral will have valuable information in real time that facilitates the communication between all the campuses of the Quito headquarters.